2010
DOI: 10.1007/s11664-010-1106-7
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence Study of Orientation-Patterned GaAs Crystals for Nonlinear Optics

Abstract: Orientation-patterned (OP) GaAs crystals are very promising for their use in nonlinear optical applications. In particular, mid-infrared and terahertz lasers can be generated by frequency conversion from shorter-wavelength sources. However, the quality of the crystals is crucial for high conversion efficiency, as the presence of defects with electrooptical signatures can contribute to optical losses. The study of these defects is a step toward the improvement of OP-GaAs crystals. We present here a spectroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Previous studies of OP-GaAs structures using cathodoluminescence (CL) indicated regions of reduced emission inside the domains located close to APBs. 3,8 We expect that some structural defects might be formed in this material. In order to provide detailed information, conventional transmission electron microscopy (CTEM) and aberration-corrected scanning transmission electron microscopy (STEM) were used for material characterization.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of OP-GaAs structures using cathodoluminescence (CL) indicated regions of reduced emission inside the domains located close to APBs. 3,8 We expect that some structural defects might be formed in this material. In order to provide detailed information, conventional transmission electron microscopy (CTEM) and aberration-corrected scanning transmission electron microscopy (STEM) were used for material characterization.…”
mentioning
confidence: 99%
“…More details on the fabrication process are given in Ref. 8. Alternatively some samples were also realized by GaAs on GaAs wafer bonding to reverse the GaAs orientation and by atmospheric pressure HVPE for the regrowth step.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On average, the last atomic column at the upper side of the boundary is As and the lower side is Ga (shown as inset), showing that the boundary is stoichiometric, despite that the microtwin having reverse growth polarity compared to the matrix. This arrangement could contribute to understand the electro-optical behavior of the inversion domain boundaries in OP crystals [1].…”
mentioning
confidence: 99%
“…In the case of oriented patterned Gallium Arsenide (OP-GaAs), which are periodic gratings of inversion domains separated by anti-phase boundaries (APBs), the quality of the crystals is crucial for high conversion efficiency in the mid-infrared and terahertz laser sources. Defects with electro optical signatures contribute to optical losses and therefore understanding them is a step toward to the improvement of the OP-GaAs crystals; in particular, the domain boundaries seem to play a major role in the efficiency conversion [1]. Therefore, a better understanding of their structure will be a step forward to reduce the optical losses.…”
mentioning
confidence: 99%